A simplified strategy based on the house of quality to prioritize farming practices under variable weather conditions. Issue 1 (2nd January 2022) - Robayo-Avendaño, Angélica; Prato-Garcia, Dorian
Abstract: This work describes for the first time a strategy based on the house of quality analysis (HOQ) to select a farming practice adaptable to variable weather conditions (VWC). Five basic requirements: water, soil, fertilizers, insecticides, and herbicides, together with six agricultural practices: organic farming (OF), agroecology (AE), conservation agriculture (CA), genetically-modified varieties (GMV), intensified agriculture (IA), and climate smart agriculture (CSA) were correlated, assessed, and prioritized. HOQ concluded that water and soil are essential for the development of a crop, whereas the need of agrochemicals was less noticeable because they could be substituted by the use of sustainable practices. OF and AE resulted more convenient because they use sustainable methods to manage a crop. The efficacy of CA and GMV to face VWC was limited by factors like the weather conditions of the site, the type of crop, and costs. IA and CSA were satisfactory when financing for the development is available. The synergy observed among OF, AE, and CA would ease transition and/or their simultaneous adoption; it would improve sustainability, productivity, and profitability for the farmer as long as the needs of the region, management of resources, and interested parties are taken into account.